Utilization of procurement process in support of takt production - Laukkarinen, Tommi Akseli (My University, 2021)
Issues related to productivity and its poor development of the construction industry are widely recognised. Lean production and lean construction developed from it have been proposed as a solution to the lagging productivity. Takt production is a location-based production controlling method developed from the principles of lean construction. This thesis seeks to identify the focal factors that affect to the lead-time of interior phase production in residential construction. These identified factors are aimed to address by means of procurement process and takt production to reduce lead-times in the future projects. Previous studies on takt production have reported promising results in reducing lead-times and improvements in productivity from the utilization of takt production. This study is executed as an exploratory case study which consists of multiple case projects of the Case Company. Data was collected from semi-structured interviews. Interviewees were both representatives of the Case Company and subcontractors. Literature review of the thesis is based on university course books, peer-reviewed scientific articles, and conference papers. Data from the interviews and literature was analysed for the conclusions of the study. Findings of the thesis indicates that takt production and procurement process can support shortening the lead-time of the interior phase production. However, there were identified factors that affects to the interior phase production that are required to be tackled for successful takt production. Support of procurement process to successful takt production arises from supplier selection, contracting, and supplier management. In this thesis, focal factors that are affecting to the lead-time of the interior phase production was identified. Based on interviews, previous studies, and the literature review solutions were presented. The findings of this thesis can be utilized in the future projects and thus implement takt production successfully with support of the procurement process to shorten lead-time of interior phase production.

Rakennusalan heikko tuottavuus ja sen kehitys ovat laajalti tunnistettu ongelma. Lean-tuotannolla ja siitä kehitetyllä lean-rakentamisella on pyritty vastaamaan tuottavuusongelmiin. Tahtituotanto on paikkakohtainen tuotannonohjausmalli, joka pohjautuu lean-rakentamisen periaatteisiin. Tämä pro gradu -tutkielma pyrkii tunnistamaan keskeiset tekijät, jotka vaikuttavat asuntorakentamisen sisävaiheen läpimenoaikaan. Tunnistettuihin tekijöihin pyritään vastaamaan hankintaprosessin ja tahtituotannon avulla läpimenoaikojen lyhentämiseksi tulevilla projekteilla. Aiemmat tutkimukset tahtituotannon hyödyntämisestä ovat osoittaneet lupaavia tuloksia lyhentämällä läpimenoaikoja ja samalla parantaen tuottavuutta. Tutkimus on toteutettu tapaustutkimuksena, jossa tutkittiin useaa Tapausyrityksen projektia. Tutkimuksen tiedot kerättiin puolistrukturoiduilla haastatteluilla. Haastateltavat olivat Tapausyrityksen ja aliurakoitsijoiden edustajia. Tutkimuksen kirjallisuuskatsaus pohjautuu Vaasan yliopiston kurssikirjoihin, vertaisarvioituihin tieteellisiin artikkeleihin ja konferenssipapereihin. Tutkimuksen johtopäätökset on tehty analysoimalla haastatteluista ja kirjallisuuskatsauksesta saatuja tietoja. Tutkimushavainnot tukevat väitettä, että tahtituotannon ja hankintaprosessin avulla sisävaiheen läpimenoaikaa voidaan lyhentää. Tutkimuksessa kuitenkin havaittiin myös sisävaiheen tuotantoon vaikuttavia tekijöitä, joiden ratkaiseminen on edellytys onnistuneelle tahtituotannolle. Hankintaprosessin tuki onnistuneelle tahtituotannolle kumpuaa toimittajavalinnasta, sopimuksien tekemisestä ja toimittajahallinnasta. Tässä tutkimuksessa tunnistettiin keskeiset sisävaiheen läpimenoaikaan vaikuttavat tekijät. Ratkaisut löydöksiin esitettiin haastattelujen, aiempien tutkimusten ja kirjallisuuskatsauksen pohjalta. Löydöksiä voidaan hyödyntää tulevilla projekteilla ja siten toteuttaa tahtituotanto onnistuneesti käyttämällä apuna hankintaprosessia sisävaiheen läpimenoajan lyhentämiseksi.
Keywords: fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master's Programme in Industrial Management